Effectiveness of a social entrepreneurship in Malaysia - the case of urban outreach - Mohd Rafi Yaacob; Mohammad Ismail; Mohd Nazri Zakaria (2015)
This study scrutinises effectiveness of a social NGOs in Malaysia in which deals with urban poverty. While government and other NGOs have looked at rural poverty, urban poverty especially amongst minority group has been sidelined. This is where NGOs could fill the void. Effectiveness of social entrepreneurship can be measured in terms of innovation and proactiveness. Urban Outreach is a pseudo name for the selected NGO. As far as this case study is concerned, Urban Outreach is effective enough. The NGO implied innovation in managerial aspects and deliveries, this is achieved because of proactiveness of staff. Organisational effectiveness of Urban Outreach is well demonstrated when it able to innovate and to act proactively eventhough it was capitalizing meager resources. This case can be used as a success factor by other organisations to run social entrepreneurship.